MicroRNA‐34a‐5p inhibits liver fibrosis by regulating TGF‐β1/Smad3 pathway in hepatic stellate cells. (10th August 2018) - Feili, Xiao; Wu, Shuang; Ye, Weiwei; Tu, Juncai; Lou, Lianqing
Abstract: Liver fibrosis is a major cause of morbidity and mortality worldwide, and the outcome of various chronic liver diseases. Recent studies suggest that aberrant expression of miR‐34 is involved in the progression of various liver diseases including hepatocellular carcinoma (HCC). However, it is still poorly understood whether miR‐34 mediates the pathogenesis of liver fibrosis. Here, we found that the expression of microRNA‐34a‐5p (miR‐34a‐5p) was significantly decreased in patients with hepatitis B virus (HBV)‐activated liver fibrosis and HCC, as well as in CC14 (Carbon tetrachloride Tetrachloromethane) induced liver fibrosis model mice. The TGF‐β1/Smad3 (Transforming growth factor‐β1/Smad3) pathway were significantly augmented in CC14 induced mice compared with normal control, whereas inhibitor of TGF‐β1 (SB431542) significantly attenuated liver fibrosis and TGF‐β1/Smad3 activation. Administration of the miR‐34a‐5p mimic de‐activated TGF‐β1/Smad3 pathway in human hepatic stellate cells (HSC), LX‐2. Moreover, the target gene for miR‐34a‐5p, Smad4, was predicted and verified in LX‐2 cells. Taken together, these data demonstrated that overexpression of miR‐34 in HSCs ameliorated the development and progression of liver fibrosis by targeting Smad4 and regulating TGF‐β1/Smad3 pathway. Strategies targeting miR‐34a‐5p may be of benefit in the treatment of liver fibrosis.